Stable and Reversible Lithium Storage Properties of LiTiOx Nanotubes for Electrochemical Recovery from Aqueous Solutions. Issue 10 (16th March 2022) - Baudino, Luisa; Zaccagnini, Pietro; Garino, Nadia; Serrapede, Mara; Laurenti, Marco; Pedico, Alessandro; Pirri, C. Fabrizio; Lamberti, Andrea
Abstract: In the present work, an easy and scalable method to prepare lithium titanium oxide nanotubes with stable and reversible lithium storage properties is reported. This material could be an excellent candidate for lithium recovery from aqueous solutions or have a direct application as Li‐ion batteries electrodes in a circular economy perspective. Vertically oriented anatase nanotubes are grown by anodic oxidation in an ethylene glycol‐based electrolyte. Then, the nanotubes are hydrothermally converted into a mixed lithium titanate. Morphological and crystallographic characterizations confirm the successful shape‐preserving conversion after which the nanotubes are subjected to electrochemical cycling. XRD and XPS analyses confirm a significant lithium uptake after cycling, and its recovery is investigated by means of an acidic treatment. While allowing for an almost complete recovery of the lithium integrated in their structure, the nanotubes also showed excellent morphological and structural stability proving to be excellent candidates for lithium recovery purposes. Abstract : Lithiated titania nanotubes show stable and reversible lithium storage properties under electrochemical conditions in an organic electrolyte. Not only do they present an impressive lithium uptake, but they are also able to release the intercalated lithium in a static acidic solution while preserving their morphology.